Exploring The Similarity of Young Entrepreneur's Financial Behavior: A Comparative Ethnographic Study of Minangnese, Javanese and Sundanese - Lidya Hamdani Putri; Agus Sugiono; Kholil Akhmad; Jerry heikal (Universitas Negeri Padang, 2024)
Wise Financial behaviors is the key to success in achieving financial stability and long-term financial goals. In managing finance, both personal and business, young entrepreneurs from a certain ethnic group can have several similarities as the key to their success in their financial behavior based on their culture. The purpose of this study is to identify patterns in cash flow management, saving, investment, debt management, insurance, and retirement preparation among the informants in managing their personal finances, as well as to conduct a comparative analysis to find similarities in financial patterns among the informants. Data were obtained through structured interviews with three informants from the Minang, Javanese, and Sundanese ethnic groups who have experience in managing their personal and business finances. The results of the analysis show that the three informants have similarities in cash flow management, such as distinguishing personal and company cash flows for control, having a monthly cash flow plan, and having a backup fund. The similarity in savings management is allocating around 10% of income to savings. The similarity in debt management is using a staggered payment system. The similarity in insurance management is following health insurance, which is BPJS Kesehatan